Création d’un manuel pédagogique comme action collaborative de promotion de l’écosanté en Asie du Sud-Est - Fèvre, Eric M.; Waltner-Toews, D.; Jing, F.; Kittayapong, P.; Adisasmito, W.; Dinh Xuan Tung; Jianchu Xu; Hung Nguyen-Viet (OpenEdition, 2014)
ABSTRACT IN ENGLISH: This paper describes the development of an Ecohealth Trainer Manual that was published in May 2013 and adapted to a Southeast Asian audience. This manual was part of a project entitled the Field Building Leadership Initiative (FBLI), launched in October 2011, which aims to build the capacity of researchers, young professionals and students in Ecohealth. The FBLI is coordinated by eight institutions in Southeast Asia and aims to tackle issues related to agricultural intensification and health. As an integral step to the development of the Trainer Manual, the FBLI invited the target audience of the manual to collaborate and network, and thereby contribute directly to the production of the teaching tools they would then be expected to use to teach Ecohealth in their respective institutions. The article describes the processes and techniques used to encourage such collaboration in the multi-institutional regional context of Southeast Asia. It suggests that three conditions are necessary to allow for the emergence of co-creation during such collaborative processes : creating an enabling environment, promoting trust and respect amongst stakeholders and participants, and sharing a common goal or common purpose. ABSTRACT IN FRENCH: Cet article décrit le processus de développement d’un Manuel pédagogique pour formateurs en écosanté publié en mai 2013 et adapté au contexte de l’Asie du Sud-Est. L’élaboration de ce manuel fait partie du projet Initiative pour la constitution du champ de recherche en écosanté (FBLI), initié en octobre 2011, et vise le renforcement des capacités de chercheurs, jeunes professionnels et étudiants de ce domaine. L’initiative regroupe huit institutions de cette région du monde autour du thème de l'intensification agricole et la santé. Le FBLI a soutenu la collaboration des professionnels impliqués dans l’écosanté pour qu’ils participent au développement d'outils qui allaient ensuite leur permettre d'enseigner l’écosanté dans leurs institutions respectives. Cet article décrit les processus mis en place pour favoriser la participation et la collaboration lors de l’élaboration de ce manuel pédagogique et de sa promotion. Seront ensuite déduits les aspects nécessaires au succès d’une collaboration productive dans un contexte régional et multi-institutionnel. Il conclut que trois conditions doivent être réunies pour parvenir à une collaboration co-créative : créer un environnement propice, promouvoir la confiance et le respect mutuel, et partager un intérêt ou un but commun.